1994
DOI: 10.1002/jmri.1880040213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of loose bodies in the elbow with MR imaging

Abstract: The evaluation of loose bodies in the elbow is usually done by means of clinical examination, radiography, and postarthrographic computed tomography (CT). The authors review their experience with magnetic resonance (MR) imaging in place of post-arthrographic CT for the evaluation of loose bodies in the elbow. The prospective interpretation of MR studies of the elbow in 20 patients was compared with arthroscopic findings. All elbows were imaged in multiple planes with thin sections, surface coils, and combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Quinn et al 32 noted that, although MRI was successful in diagnosing 100% of cases of intraarticular loose bodies of the elbow, the specificity was only 67%. Other authors have suggested that the absence of elbow effusion and the small size of loose bodies may decrease the sensitivity of MR imaging, whereas osteophytes and synovial hypertrophy may mimic loose bodies.…”
Section: Specific Applicationsmentioning
confidence: 99%
“…Quinn et al 32 noted that, although MRI was successful in diagnosing 100% of cases of intraarticular loose bodies of the elbow, the specificity was only 67%. Other authors have suggested that the absence of elbow effusion and the small size of loose bodies may decrease the sensitivity of MR imaging, whereas osteophytes and synovial hypertrophy may mimic loose bodies.…”
Section: Specific Applicationsmentioning
confidence: 99%
“…MRI is expensive and observers have difficulty in differentiating between osteophytes and loose bodies. 7 Quinn et al 7 reported a sensitivity of 100% and a specificity of 67%. We report excellent sensitivity but a low to moderate specificity for the posterior compartment.…”
Section: Discussionmentioning
confidence: 99%
“…MRI has become popular for diagnosing loose bodies in the elbow. 6,7 The benefits include multiple plane imaging, the avoidance of radiation and the diagnosis of primarily cartilaginous lesions and other lesions such as osteochondritis dessicans. MRI is expensive and observers have difficulty in differentiating between osteophytes and loose bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ce bilan radiographique standard a une sensibilité de 79 % et une spécificité de 69 % [1]. L'arthrographie en revanche est très sensible (100 %) mais peu spécifique (71 %) tout comme l'IRM [1,2].…”
Section: éTiologie Clinique Et Bilanunclassified